PEMANFAATAN BATU ZEOLITE SEBAGAI AGREGAT KASAR PADA CAMPURAN ASPHALT CONCRETE BINDER COURSE (AC-BC) DENGAN BAHAN IKAT ASPAL PERTAMINA PEN 60/70 DAN STARBIT E-60 - Subarkah Subarkah; Helmy Akbar Bale; Adyatma Arif Nugraha (TEKNISIA, 2020)
In the construction project, especially the roads in Yogyakarta and surrounding areas, the aggregate used is derived from the Clereng Kulonprogo. This amount of aggregate usage results in scarcity and affects the price to become expensive. The use of coarse aggregate materials as an alternative is rare. In reality, it is necessary to make innovation by utilizing the coarse aggregate of zeolite stone, which is still quite widely available in the Klaten area. Based on the preliminary test, the zeolite aggregate has a lower abrasion resistance compared to the andesite aggregate from Clereng. Using a modified asphalt Starbit E-60, which has a deficient penetration value, is expected to provide better stability to compensate for the weakness of zeolite stones. A combination of a mixture between a coarse aggregate of zeolite Stones and Andesite is tested until how large the proportion of zeolite stones of such combinations can provide the optimum value to AC-BC layer pavement. This research compares the performance of the AC-BC mixture using zeolite and andesite stones. It determines the feasibility of zeolite's stone, in substituting the andesite stone, in the AC-BC mixture. It is also to know the influence of the use of Starbit E-60 in the AC-BC mixture. The comparison of those performances was referred to as Marshall characteristics, Indirect Tensile Strength (ITS), and Immersion; using Pen asphalt Pen. 60/70 and Starbit E-60 as a binder. Trial mix was applied to the bitumen content variation of 5%, 5.5%, 6%, 6.5%, to determine Optimum Bitumen Content (OBC) by conducting Marshall testing. The variety of substitution zeolite proportions of 0%, 25%, and 75% was made in each trial mix above. The research result showed that the maximum percentage of zeolite aggregate in the mixture using an asphalt Pen 60/70, which meets with specification standard, is 28%, while the mixture using Starbit E-60 is 26%. ITS value decreases as the percentage of zeolite are increased. ITS value of mix with Starbit E-60 is higher than that of mix with asphalt Pen 60/70. Cantabro Loss value increases with zeolite proportion increase, for both mixed with Starbit E-60 and asphalt Pen 60/70. Cantabro loss of mix with Starbit E-60 is lower than that of with asphalt Pen 60/70. IRS value decrease with an increasing proportion of zeolite.